Analisis pengaruh kinerja keuangan terhadap cash dividend pada perusahaan manufaktur yang terdaftar di Bursa Efek Indonesia (BEI) - Tama, Fareza Wisnu Aji (CV. Kurnia Grup, 2023)
This research is intended to know and prove the influence of financial performance towards devident cash on manufacturing industries between 2008 -2011 listed in indonesian stock exchange. And also to measure the degree of influence between financial performance towards cash dividend, thus we used return on investment (ROI) debt to total assets (DTA) and earning per share (EPS) as an indicator that give influence towards cash dividend. We used all manufacturing industries listed in Indonesia stock exchange as a population to calculate the outcome of this research. However, during the research we used purposive sampling method to gather the data and in this case there are 152 companies eligible to be classified as good samples of this research. Then we also used SPSS as a tool to calculate statistical test of regression analysis. Based on the data above, we only found that debt to total assets (H3) did not not prove any significant relationship toward cash dividend. However the rest of the proposed hypothesis (H1, H2, H4 and H5) that consist of return on investment, current ratio and earning per share do have significant relationship toward cash dividend. In the other hand all proposed hypothesis’ have significant and positive relationship toward cash dividend simultaneously. During the statistical calculation we also found that independent variable influences as much as 20,7 % toward cash dividend showed in Adjusted R2 calculation and 79,3 % is influenced by other variables outside this research.